AI and Human Collaboration in Claims Processing: Optimizing the Hybrid Approach for Healthcare Payers - Uday Bag (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
AI is revolutionizing claims adjudication while maintaining essential human oversight in healthcare payment systems. This article examines the symbiotic relationship between advanced AI technologies and human expertise in modern claims processing. By exploring implementations at leading insurers like AmeriHealth, Cigna, and Blue Cross, we demonstrate how this collaborative approach enhances accuracy, prevents fraud, and ensures regulatory compliance. The integration of machine learning for pattern recognition, natural language processing for documentation review, and human judgment for complex determinations creates a robust framework that balances efficiency with quality care. Healthcare payers seeking to optimize their claims operations will discover actionable strategies for implementing hybrid systems that leverage the strengths of both artificial intelligence and human specialists while navigating the evolving regulatory landscape.
Keywords: Claims Adjudication; Artificial Intelligence; Healthcare Compliance; Fraud Detection; Human-AI Collaboration